2015
DOI: 10.1038/cddis.2015.216
|View full text |Cite
|
Sign up to set email alerts
|

Scaffolding protein Homer1a protects against NMDA-induced neuronal injury

Abstract: Excessive N-methyl-D-aspartate receptor (NMDAR) activation and the resulting activation of neuronal nitric oxide synthase (nNOS) cause neuronal injury. Homer1b/c facilitates NMDAR-PSD95-nNOS complex interactions, and Homer1a is a negative competitor of Homer1b/c. We report that Homer1a was both upregulated by and protected against NMDA-induced neuronal injury in vitro and in vivo. The neuroprotective activity of Homer1a was associated with NMDA-induced Ca2+ influx, oxidative stress and the resultant downstream… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 69 publications
0
29
0
Order By: Relevance
“…Increased Homer1a expression attenuated neuronal injury induced by mGluR1 activation in a model of traumatic brain injury (Luo et al, 2014) and reduced Ca 2+ overload and neuronal injury in a MPP(+)-toxicity model with cultured rat mesencephalic cells (Zeng et al, 2013). Increased Homer1a expression was also recently demonstrated to exert neuroprotective effects against NMDA-induced neuronal injury (Wang et al, 2015b). Interestingly, expression of homer1a has been shown to be elevated following inhibition of neuronal SOC in PC12 cells, suggesting potential cross-talk between SOC and Homer1a expression in neuronal cells (Li et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Increased Homer1a expression attenuated neuronal injury induced by mGluR1 activation in a model of traumatic brain injury (Luo et al, 2014) and reduced Ca 2+ overload and neuronal injury in a MPP(+)-toxicity model with cultured rat mesencephalic cells (Zeng et al, 2013). Increased Homer1a expression was also recently demonstrated to exert neuroprotective effects against NMDA-induced neuronal injury (Wang et al, 2015b). Interestingly, expression of homer1a has been shown to be elevated following inhibition of neuronal SOC in PC12 cells, suggesting potential cross-talk between SOC and Homer1a expression in neuronal cells (Li et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Due to these structural features, Homer1a acts as a dominant-negative protein that disrupts the complexes formed by long Homers and regulates downstream signaling (Xiao et al, 2000 ). Our previous studies have demonstrated that Homer1a protects neurons against various stresses by regulating metabolic glutamate receptors, N-methyl-D-aspartate receptors, and store-operated calcium entry (Luo et al, 2014 ; Wang et al, 2015 ; Rao et al, 2016 ). We also found that Homer1a attenuates H 2 O 2 -induced oxidative stress by reducing ROS accumulation in PC12 cells (Luo et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…One protein that may play an important role in glutamate-induced calcium dysregulation is Homer1a, an intensively-studied immediate early gene (IEG) that belongs to the postsynaptic protein family. Previous studies have demonstrated that Homer1a is extensively involved in neuronal calcium signals, affecting not only metabolic glutamate receptors (mGluR), but also iGluRs, particularly N-methyl-D-aspartate receptor 12 13 14 15 16 . These functions are mostly attributed to its structural features.…”
mentioning
confidence: 99%
“…Additionally, the inhibition of SOCE alleviated oxidative stress-induced cell injury in HT-22 cells by reducing calcium influx 8 26 . Because Homer1a lacks the CC domain, and therefore cannot self-multimerize, Homer1a might act as a negative competitor of Homer1b/c, disturbing the Homer1b/c-calcium channel complexes, and therefore play a role in the cell’s response to oxidative stress 12 13 27 . However, whether Homer1a plays a role in glutamate-induced HT-22 injury or can alter glutamate-induced calcium influx has not been elucidated.…”
mentioning
confidence: 99%